Reduced rank regression-derived dietary patterns related to the fatty liver index and associations with type 2 Diabetes Mellitus among Ghanaian populations under transition: the RODAM study - Osei, Tracy Bonsu; van Dijk, Anne-Marieke; Dingerink, Sjoerd; Chilunga, Felix Patience; Beune, Erik; Meeks, Karlijn Anna Catharina; Bahendeka, Silver; Schulze, Matthias Bernd; Agyemang, Charles; Nicolaou, Mary; Holleboom, Adriaan Georgius; Danquah, Ina (Nutrients, 2021)
The Fatty Liver Index (FLI) is a proxy for the steatotic component of non-alcoholic fatty liver disease (NAFLD). For sub-Saharan African populations, the contribution of dietary factors to the development of NAFLD in the etiology of type 2 diabetes mellitus (T2DM) remains to be clarified. We identified sex-specific dietary patterns (DPs) related to the FLI using reduced ranked regression (RRR) and evaluated the associations of these DPs with T2DM. This analysis used data from the RODAM, a multi-center cross-sectional study of Ghanaian populations living in Ghana and Europe. The daily intake frequencies of 30 food groups served as the predictor variables, while the FLI was the response variable. The odds ratios and 95% confidence intervals for T2DM were calculated per one standard deviation increase in the DP score using logistic regression. In males, the DP score explained 9.9% of the variation in their food intake and 16.0% of the variation in the FLI. This DP was characterized by high intakes of poultry, whole-grain cereals, coffee and tea, condiments, and potatoes, and the chance of T2DM was 45% higher per 1 DP score-SD (Model 2). Our results indicate that the intake of modernized foods was associated with proxies of NAFLD, possibly underlying the metabolic pathways to developing T2DM.